Pemberdayaan Masyarakat Kawasan Konservasi Kramat, Bedil, dan Temudong melalui Pengembangan Ekowisata Bahari dan Budi Daya Rumput Laut - Dedi Syafikri; Siti Nurwahidah; Neri Kautsari (Institut Pertanian Bogor, 2019)
Kramat, Bedil, and Temudong (KBT) islands are watershed conservation areas located in Sumbawa Regency precisely in Labuhan Bajo Village. The main problem is the prohibition of fishing in some conservation zones, thereby reducing the area of fishing. Reduced of catchment area directly affects the decrease in catches and community income. Therefore, as an effort to overcome these problems, it is necessary to optimize the utilization of other zones in the conservation area. Sustainable fisheries zones and tourism zones are zones that have not been optimally utilized. This zones has the potential for ecotourism and seaweed cultivation, but most people do not have the knowledge and skills in the development of ecotourism and seaweed cultivation. The program aims to train and assist the community in integrating ecotourism with seaweed cultivation in sustainable fisheries zones, so that it can be an alternative livelihood for the local community. the program has outcomes that consist of: the availability of alternative livelihoods for people in conservation areas based on the integration of ecotourism and seaweed cultivation, increasing community income, and building positive community perceptions for conservation activities. The method used is counseling, training and mentoring on the development of marine ecotourism and Eucheuma cottonii seaweed cultivation in the sustainable fishing zone. The results of this activity are the development of marine ecotourism in the KBT MPA as evidenced by an increase in the number of visitors (tourists) three times more than before, the availability of alternative livelihoods of the community through boat rentals and increased knowledge and skills of the community in seaweed cultivation.